Criteria for Improving the Economic Activity of Youth (Czech Journal of Multidisciplinary Innovations, 2022)
The article examines the issues of creating economic values, economic activation of young people, taking a number of measures in this regard, moralizing and aestheticizing issues in increasing economic activity of young people. Also, the possibilities of economic activation of youth in the society and systematic study of their problems, scientific-practical analysis are presented.